Al-Qisas Fi ma Duna al-Nafs Bayna al-Ab wa Ibnihi fi Dhaw'i Nazariyyah al-Ta'assaf fi Isti'mal al-Haq fi al-Fiqh al-Islami - Hammad, Hamza Abed al-Karim (Jurnal Fiqh, 2011)
The purpose of this study is to explain the perspective of Islamic jurisprudence from the retaliation between father and his son. The research conducted explaining this case between schools of Islamic jurisprudence. Furthermore, studied also utilized the norms of theory of abuse of right in Islamic jurisprudence. The result of this study explained that there is retaliation of father if he attacked his son, but he guaranteed all damages and there is retaliation from the son.